DEVELOPMENT OF HOSPITAL INFECTIOUS WASTE MANAGEMENT RISK ASSESSMENT USING THE FAILURE MODE AND EFFECT ANALYSIS (FMEA METHOD) CASE STUDY BANDUNG REGIONAL HOSPITAL - Fitria, Novi
Hospital infectious waste has become an important issue because of the potential and risk of exposing the disease to both patients, hospital workers, and the people living around the hospital. Risk assessment in infectious waste management systems is divided into two methods, namely (1) a qualitative risk analysis that identifies risks descriptively, (2) a quantitative risk analysis that identifies risks by using calculations to obtain risk prioritization starting from the process of sorting, collecting, transporting, storage to disposal process. Currently, in Indonesia the regulations governing the procedures for handling hazardous waste from health service facility activities have been contained in the LHK Ministerial Regulation. P56/2015, but a comprehensive study to evaluate its implementation and its correlation to risk assessment has not been comprehensively reviewed. This study aims to identify and evaluate the suitability of hospital infectious waste management with applicable regulations and develop a risk assessment framework with the FMEA method approach in hospital infectious waste management systems. This study consists of 4 stages, namely the first stage was to estimated the generation, the proportion of infectious waste and identified the factors that influenced it and observed the existing conditions of hospital infectious waste management. The second stage was to identified and evaluated hospital infectious waste management against applicable regulations also compared and evaluated infectious waste management between developing country and developed country. The third stage was to identified risks and assessed risks qualitatively and then developed them into quantitative risk assessments used FMEA method. The fourth stage was followed by the development of an integrated risk assessment framework for infectious waste management, covering aspects of policies or regulations as well as operational technical aspects, so that risk prioritization and recommendations can be carried out. The first phase of the study through direct sampling obtained estimates of infectious waste generation from 7 hospitals was 317.1 kg/day with the proportion of infectious waste 30.4% of total hospital waste. The generation rate of infectious waste in inpatient facilities was 45 ± 39.5 kg/day; 0.4 ± 0.2kg/ TT/day and 0.7 ± 0.5kg/occ.TT/day. The generation and proportion of infectious waste was significantly affected by the type of hospital. Type C hospitals gave significantly higher infectious waste generation compared to hospitals type A, B and D. It is identified that the generation of infectious waste was not linear to the type of hospital, it was influenced by medical actions taken on patients. So it did not guarantee the higher type of hospital caused the higher generation rate of infectious waste. The high generation and proportion of infectious waste from inpatient room was due to the disposal of non-infectious waste that was combined with infectious waste in study area. The second phase of the study focused on the percentage of compliance of hospital infectious waste management based on EPA/1992 and LHK Regulation p56/2015. Data collection was conducted by using a checklist method. The average % of compliance in managing infectious waste from 7 hospitals was 57% and 59%. Whereas at Radboud UMC gave 97% compliance in hospital infectious waste management based on EPA/1992 and 90% based on LHK Permen p.56/2015. The hospital profile that influences the compliance of infectious waste management was the type of hospital, the accreditation status and the status of cleaning staff with p value < 0.05. As for the proportion and generation rate of infectious waste, the% compliance of infectious waste management was had strong correlation influence due to correlation coefficient (r) 0,8801 and 0.7073 in kg/day unit. The low level of compliance of hospital infectious waste management in the Bandung area shows the potential for a higher risk to the health of officers, patients and hospital visitors by infectious diseases compared to that in Radboud UMC Netherlands. Functional systems for sorting, contingency planning and disposal of infectious waste give a % compatibility less than 50% with respectively value of 28.4%; 33.3% and 42.9%. The third phase of the study identified the forms of failure modes in managing infectious waste. Data obtained through questionnaires filled out by 125 respondents who work in hospitals with the profession of doctors, office staff, pharmacists, midwives, health workers, cleaning services and analysts with 53% of respondents work in the study area and 47% of respondents work outside the study area. The results indicated potential risks in managing infectious waste in the process of sorting, collecting, storing, human resources and SOP. Identification of failure modes was accumulated and 55 failure modes were determined for the FMEA instrument. The risk assessment category consists of severity, occurrence and detection. Multiplication of severity, occurrence and detection were called the risk priority number (RPN). In this study values of severity, ooccurrence and detection was developed by a scale of categories 1 to 5. The fourth phase of the research was carried out a risk assessment using the FMEA approach. The development of risk assessment frameworks and instruments in this study consists of: (1) the use of Regulation on LHK Regulation No. p.56/2015 as a standard for evaluating hospital infectious waste management and determining 9 (nine) functional systems of infectious waste management processes; (2) addition of hospital profile variable in the sample as a basis for inventory failure modes; (3) determining the severity, occurrence and detection value categories on a scale of 1-5; (4) testing the FMEA instrument; (5) FMEA instrument validation test. The total value of RPN with variable hospitals varies between 700 - 2348, where hospitals that have not been accredited provide the highest risk value in managing infectious waste. The total functional system variable RPN varies between 344- 1425, where the infectious waste disposal process provides the highest risk value with a total RPN of 1425 and is followed by the storage process of infectious waste with a total RPN 1420. Risk Priority Number (RPN) was influenced significantly by hospital type, hospital accreditation status, ownership status, janitor status with p value <0.05. The validation test results of the FMEA instrument showed a significant relationship between the % suitability of infectious waste management with the RPN value where the correlation coefficient (r) 0.9368.